Nilai Filosofi Gerak Tari Guel pada Masyarakat Gayo di Kota Takengon Kabupaten Aceh Tengah - Maghfhirah Murni Bintang Permata; Indra Setiawan; Rika Wirandi (Universitas Negeri Medan, 2020)
Guel dance was a traditional dance based on the history narrative of Gayo, District- inspired by the legend of the siblings Sengedaand BenerMerie who were looking for white elephants that to be presented to a princess. Therefore, some elements of the dance movements reflected the character of the elephant. Besides the aspect of form, every element of Guel dance movements also contained the philosophical values that contain moral messages and social values. Currently, Guel dance performances creations are increasingly present in the middle of the community, The forms of Guel dance creations sometimes leave the standard provisions as a standard form of the dance itself. This study aimed to describe the philosophical values of the Guel dance movement in Takengon, Aceh Tengah District, by using the theory approach of motion dance structure fromKaepleer. The method used in this study was descriptive interpretative approach, namely research directly related to the community (participatory observation)for data retrieval. This study concluded that the Guel dance was a traditional dance which has a standardize story structure and dance motion philosophy. It implied the moral teachings, religious teachings, Guel dance has a message about loyalty, responsibility, fraternity, and it is not only done by relatives or family nut must be done in relationship for others.